The Implementation of the Cultuurstelsel in Java: Cases in Afdeeling Demak and Grobogan, Central Java versus in Afdeeling Pacitan, East Java 1830-1870 - Iswahyudi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The Dutch colonial government in applying the Cultuurstelsel policy in Java in 1830 used traditional Javanese patterns of power to persuade farmers in certain regions to be willing to work in export plantations and surrender a portion of their land to be planted with governorate crops. Based on the description above, it would be interesting to see further about the implementation of the cultivation system in several afdeeling areas or regencies in Java because in Pacitan, East Java, it is said to have an impact on prosperity and welfare for farmers. On the other hand, in other regions, in Afdeeling Demak and Grobogan, Central Java, the opposite happened, namely that the implementation of the forced cultivation system actually had an impact on misery and poverty among the population. Regardless of whether Cultuurstelsel should be valued positively or negatively, most historians agree that the system had been one of the most important parts of Dutch colonialism in the Dutch East Indies from 1830 to 1870. Some at that time even thought that cultuurstelsel was the best colonial model that can be imagined.